2016
DOI: 10.1186/s12936-016-1088-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and entomological studies of a malaria outbreak among French armed forces deployed at illegal gold mining sites reveal new aspects of the disease’s transmission in French Guiana

Abstract: Background In December 2010, a Plasmodium vivax malaria outbreak occurred among French forces involved in a mission to control illegal gold mining in French Guiana. The findings of epidemiological and entomological investigations conducted after this outbreak are presented here.MethodsData related to malaria cases reported to the French armed forces epidemiological surveillance system were collected during the epidemic period from December 2010 to April 2011. A retrospective cohort study was conducted to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Anopheles adult female mosquitoes were selected from field mosquito collections done in 6 distinct sites from French Guiana, during entomological surveys, using different collection methods, over different sampling periods (Figure 1) [3,3941]. After collections, mosquitoes were sorted by genera and Anopheles mosquitoes were morphologically identified under a binocular loupe at a magnification of ×56 (Leica M80, Leica, Nanterre, France) using standard taxonomic keys for the region (Floch and Abonnenc 1951, Forattini 1962, Faran and Linthicum 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Anopheles adult female mosquitoes were selected from field mosquito collections done in 6 distinct sites from French Guiana, during entomological surveys, using different collection methods, over different sampling periods (Figure 1) [3,3941]. After collections, mosquitoes were sorted by genera and Anopheles mosquitoes were morphologically identified under a binocular loupe at a magnification of ×56 (Leica M80, Leica, Nanterre, France) using standard taxonomic keys for the region (Floch and Abonnenc 1951, Forattini 1962, Faran and Linthicum 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Vector-borne diseases constitute a major threat to the operational capacity of armed forces personnel operating outside or stationed overseas. In past years, the military health service participated in monitoring the entomologic status of French military bases in sub-Saharan Africa (Gabon, Ivory Coast, Republic of Central Africa, Senegal, Djibouti) and focused on French Guiana [2] , [3] , [4] , [5] , [6] , [7] , [8] . This surveillance included the identification of vectors, the study of behaviour and the evaluation of insecticide resistance and enabled the development or improvement of new tools for vector trapping [9] , [10] , vector identification such as molecular and proteomic methods [11] , [12] , pathogen identification in vectors [13] , [14] or identification of markers of resistance to insecticides [2] , [3] .…”
Section: Recent Achievements In Vector-borne Diseasesmentioning
confidence: 99%
“…In order to better characterize the risk of naturally acquired infections, epidemiologic studies are conducted in French armies and their neighbourhood. For example, investigations have been conducted after the occurrence of malaria outbreaks among French forces involved in missions to control illegal gold mining in French Guiana [7] . The epidemiologic and entomologic studies conducted in these remote and dangerous areas have demonstrated that illegal gold mining sites must be considered to be high-level malaria transmission areas.…”
Section: Recent Achievements In Vector-borne Diseasesmentioning
confidence: 99%
“…Plasmodium vivax is the predominant malaria parasite species and was responsible for 80% of the diagnosed cases in 2015, with the remainder mainly due to P . falciparum [ 21 24 ]. Most malaria cases are reported in villages located along the main rivers flowing through the territory and in illegal gold mining areas, which are propitious places for malaria transmission [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%